Evangelicals in Democratic Chile, 1990-2008: From Resistance Identity to Project Identity 1 - Fediakova, E (2012)
Since the reestablishment of democracy in Chile, Evangelicals have been becoming more prominent in society. Their communities foster civic skills among their members, and this fact, taken together with the gradual raising of their economic and educational level, could transform the Evangelicals into a cultural citizenship . Nevertheless, my study project shows that in spite of the extensive community work that Evangelical churches are developing, and their respect for democracy, they continue to be depoliticised and distanced from the main national problems. The Evangelical community is concerned about its rights, but it tends to act in defence of its corporate interests rather than in the national perspective, which decreases its involvement in the developing democracy. © 2012 Copyright Taylor and Francis Group, LLC.